2013
DOI: 10.3892/ijo.2013.2021
|View full text |Cite
|
Sign up to set email alerts
|

Plasma endothelial protein C receptor influences innate immune response in ovarian cancer by decreasing the population of natural killer and TH17 helper cells

Abstract: In spite of the growing importance of endothelial protein C receptor/active protein C (EPCR/aPC) in tumor biology, their impact on immunological homeostasis remains largely unexplored. The objective of this study was to assess whether soluble plasma endothelial protein C receptor (sEPCR), which is a regulator of circulating aPC, is involved in innate immune response in cancer patients. In the Ovcar-3 ovarian cancer line, the role of aPC in secretion of cytokines was analyzed. In parallel, in 33 patients, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…In contrast no TPO was extracted from breast cancer cell line (MDA-MB231), compared with ovarian or leukemic cells. Previously we found that when OVCAR-3 cells were incubated with activated protein C, the cancer cell migration was upregulated via MEK-ERK and Rho-GTPase pathway signalization [31] and the amount of secreted TPO in the culture medium detected by cytokine array increased four times [22]. In nonpublished results, we also demonstrated that activated protein C and, to a lesser degree, protein C induced the microparticles release in OVCAR-3 cell line.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In contrast no TPO was extracted from breast cancer cell line (MDA-MB231), compared with ovarian or leukemic cells. Previously we found that when OVCAR-3 cells were incubated with activated protein C, the cancer cell migration was upregulated via MEK-ERK and Rho-GTPase pathway signalization [31] and the amount of secreted TPO in the culture medium detected by cytokine array increased four times [22]. In nonpublished results, we also demonstrated that activated protein C and, to a lesser degree, protein C induced the microparticles release in OVCAR-3 cell line.…”
Section: Discussionsupporting
confidence: 52%
“…We also observed that activated protein C (aPC), a natural anticoagulant, increased OVCAR-3 TPO secretion [22]. …”
Section: Introductionmentioning
confidence: 99%
“…On endothelial cells, the aPC, together with its cofactor protein S, degrades factors Va and VIIIa and thereby interferes with thrombin generation and abolishes the coagulation cascade ( 12 ). Endogenous aPC is shown to limit cancer cell extravasation through S1P-1-mediated vascular endothelium ( 13 ) and also plays a role in innate immune system ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the Th17 profile is involved with increased immunity and host defenses, its involvement in neoplastic processes remains controversial (6,10). Previous studies suggest that Th17 cells are involved in cancer promotion (11)(12)(13)(14)(15). Notably, in the tumor microenvironment, Th17 cells have been observed to positively correlate with immune effector cells, including CD8+ T cells and natural killer cells, promoting an antitumor response that is mediated by cytotoxic cells (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggest that Th17 cells are involved in cancer promotion (11)(12)(13)(14)(15). Notably, in the tumor microenvironment, Th17 cells have been observed to positively correlate with immune effector cells, including CD8+ T cells and natural killer cells, promoting an antitumor response that is mediated by cytotoxic cells (11,12). As a result of the production of pro-inflammatory cytokines by Th17 cells that accumulate in the tumor microenvironment, and the association between the development and progression of cancer, a positive correlation between these cells and disease progression has been hypothesized (13,14).…”
Section: Introductionmentioning
confidence: 99%